(untitled) (Global Journal of Management and Business Research, 2014)
Quality of work life is a comprehensive approach of work life that holds some sorts of principles those are job satisfaction, trustworthiness toward organization and valuable contribution of workforce for the organizations. In spite of banking sector of Bangladesh is a growing and emerging economic sector, the state owned commercial banks are not contributing to the economy up to marks. The objective of the study is to analyze the interrelationship between the quality of worklife and the dimensions or factors of quality of worklife on the bank employees in the northern region of the country. A structured self administered questionnaire consists of 20 items have been used for primary data collection. Secondary data have been derived from the books, published research articles, and banks websites for achieving the objectives of the study. The survey data have been analyzed using SPSS. The descriptive analysis, correlation test, and regression analysis have been used to analyze the collected data. The study has found that in the banks there is a little presence of environment of quality of worklife. Basically there is a strong need of suitable working environment and presence of hazy work features and a little existence of social recognition and integration and the rest of the dimensions are moderately present. The study has also revealed that compensation and other remuneration and career opportunity and growth are highly correlated with worklife that causes a lower level of satisfaction of employees’ comparison to private commercial banks’ employees.